1978
DOI: 10.1042/bj1700583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-alanine infusion on gluconeogenesis and ketogenesis in the rat in vivo

Abstract: 1. In 48 h-starved 6-week-old rats the 14C incorporation in vivo into blood glucose from a constant-specific-radioactivity pool of circulating [14c]actateconfirmed that lactate is the preferred gluconeogenic substrate. 2. Increasing the blood [alanine] to that occurrring in the fed state increased 14C incorporation into blood glucose 2.3-fold from [14c]alanine and 1.7-fold from [14c]lactate. 3. When the blood [alanine] was increased to that in the fed state, the 14C incorporation into liver glycogen from circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Although NEFA may suppress glucagon secretion [30], whether this was the case in the present studies cannot be established. However, the results of the present studies are concordant with earlier data indicating that the formation of ketone bodies is reduced by the elevation of plasma alanine, as shown in rats [31,32] and man [33]. These studies point towards a clear anti-ketogenic effect of alanine in the setting of a reciprocal relationship between alanine and ketone bodies (alanine-ketone body cycle) [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…Although NEFA may suppress glucagon secretion [30], whether this was the case in the present studies cannot be established. However, the results of the present studies are concordant with earlier data indicating that the formation of ketone bodies is reduced by the elevation of plasma alanine, as shown in rats [31,32] and man [33]. These studies point towards a clear anti-ketogenic effect of alanine in the setting of a reciprocal relationship between alanine and ketone bodies (alanine-ketone body cycle) [33,34].…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in blood ketone-body concentration caused by alanine was confirmed in the rat by Ozand et al (1977), who showed that the effect was unchanged by the presence of anti-insulin serum, suggesting more directly that insulin was not involved in the phenomenon. A notable finding of Ozand et al (1977Ozand et al ( , 1978 was that the antiketogenic effect was restricted to 3-hydroxybutyrate with blood acetoacetate concentrations remaining unchanged or even increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose, lactate, pyruvate, alanine, acetoacetate and 3-hydroxybutyrate were analysed by a microautoanalytic procedure previously described (Ozand et al, 1976a). L-Alanine was assayed by using alanine dehydrogenase in experiments involving dichloroacetate (Yoshida & Freese, 1970;Ozand et al, 1976a). Unesterified fatty acids were measured colorimetrically (Lauwreys, 1969).…”
Section: Analysesmentioning
confidence: 99%
“…At the indicated intervals, 50,pl of arterial blood was quickly withdrawn and mixed with 600,1l of 1M-HCl04 at 0°C. The supernatant fluids were removed and kept at -95°C until analysed (Ozand et al, 1976a). Since the volume in the arterial catheter was approx.…”
Section: Perfusion Proceduresmentioning
confidence: 99%